Environmental relevant concentrations of copper sulphate induce biochemical and molecular toxicity in Labeo rohita - Saima Naz; Riaz Hussain; Hafiz Muhammad Ali; Nasir Masood; Ghazala Jabeen; Rehana Iqbal; Momil Liaquat; Muhammad Irfan Ullah; Kashif Hussain; Tuğçe Merve Berberoğlu; Ahmed A. El-Mansi; Eman A. Elbealy; et al. (PLoS ONE, 2025)
Copper is an important element involved in the catalysis of many vital reactions in the body of an organism. However, excessive copper causes cellular damage by accelerating the production of reactive oxygen species and disrupting the physiological reactions. The present research was conducted to determine the toxicological effects including oxidative stress profile, concentrations of anti-oxidant enzymes and genotoxicity of three different doses (0.28 µg/L, 0.42 µg/L and 0.56 µg/L) of copper sulphate (CuSO4) subjected to Labeo rohita for 36days. Micronucleus test indicated a significant (p < 0.05) increase in the frequency of morphological and nuclear changes in the erythrocytes of the treated fish. A significant (p < 0.05) increase was observed in oxidative stress parameters (ROS, TBARS) whereas the activity of anti-oxidant enzymes (SOD, POD, GSH, CAT) was significantly (p < 0.05) decreased in the gills, brain, liver and kidneys of fish exposed to 0.56 µg/L concentration of CuSO4. Moreover, CuSO4 exhibited significant (p < 0.05) DNA damage in lymphocytes, brain cells, hepatocytes and renal cells, as determined by comet test. Hence, it has been concluded that CuSO4causesevere biochemical and physiological disruptions in different organs of Labeo rohita, hence, considered as hazardous even at very low sub-lethal concentrations.